A review of diesed emission monitoring and control technology - I S. Lowndes; K. Moloney (The Institute of Materials, Minerals and Mining, 1996)
Diesel powered equipment is currently used extensively in mining and tunnelling operations around the world due to its mobility, flexibility and through selective application to enhance productivity. However, the increased use of diesel equipment has exacerbated the pollutant load (including heat, humidity, exhaust gases and particulates) placed upon the environmental systems of many underground operations. This expansion in the use of diesel equipment has prom pted researchers to evaluate m easure ment and control technology. This paper reviews the recent research conducted in various countries.